Keterampilan Membuka Pelajaran Mahasiswa Semester 6 pada Mata Kuliah Kemampuan Dasar Mengajar - Adi (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
This study aims to determine the ability of students to open learning in the English Education Study Program, sixth semester in the subject of basic teaching skills. The method used in this study is a qualitative descriptive method with an observation sheet instrument and an assessment rubric, from the results of this study it can be obtained data on opening skills as follows: Motivation Indicators & Attracting Students' Attention = Less Score: 0%, sufficient: 6%, good : 61% and excellent: 33%. Indicators provide a reference: Poor score: 35%, adequate: 37%, good: 28% and very good: 0%. And the indicators make the connection: Poor score: 0%, adequate: 50%, good: 41% and very good: 9%. In the second practice after the evaluation, the scores were obtained as follows: Motivation Indicator & Attracting Student Attention = Poor Score: 0%, adequate: 0%, good: 50% and very good: 50%. Indicators provide a reference: Poor score: 0%, adequate: 28%, good: 39% and very good: 33%. And indicators make the connection: Poor score: 0%, adequate: 0%, good: 61% and very good: 39%. From these results it can be concluded that the ability to open lessons in semester 6 students of the 2021/2022 academic year is good.